2007
DOI: 10.1088/0031-9155/52/23/026
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination ofpCoperturbation factors for plane-parallel chambers

Abstract: For plane-parallel chambers used in electron dosimetry, modern dosimetry protocols recommend a cross-calibration against a calibrated cylindrical chamber. The rationale for this is the unacceptably large (up to 3-4%) chamber-to-chamber variations of the perturbation factors (pwall)Co, which have been reported for plane-parallel chambers of a given type. In some recent publications, it was shown that this is no longer the case for modern plane-parallel chambers. The aims of the present study are to obtain relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The theoretical explanation for a wall perturbation correction larger than unity is the electron backscatter deficiency of the wall materials in comparison to water (Hunt et al 1988, Klevenhagen 1991. According to Klevenhagen, the electron backscatter is proportional to the effective atomic number of the scatterer and inversely proportional to the electron energy.…”
Section: Perturbation Corrections In Electron Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical explanation for a wall perturbation correction larger than unity is the electron backscatter deficiency of the wall materials in comparison to water (Hunt et al 1988, Klevenhagen 1991. According to Klevenhagen, the electron backscatter is proportional to the effective atomic number of the scatterer and inversely proportional to the electron energy.…”
Section: Perturbation Corrections In Electron Beamsmentioning
confidence: 99%
“…The discussion about perturbation corrections for parallel-plate chambers in clinical electron beams has a long history. More than 20 years ago, the electron backscatter from different materials and the implication for electron dosimetry was investigated byKlevenhagen et al (1982), Klevenhagen (1990Klevenhagen ( ), (1991 and Hunt et al (1988). From their backscatter measurements using different materials, they concluded that there is an energy dependence under response of parallel-plate chambers in the range of 1%-2% due to a backscatter deficiency of the chambers rear wall in comparison to water.…”
Section: Comparison With Literature Datamentioning
confidence: 99%
“…This recommendation, which avoids the need for a calculated (generic) kecal factor, is based on early evidence that minor construction details significantly affect the response of these chambers in cobalt‐60 beams, which would give rise to higher uncertainties in calculations of kecal. More recent publications have demonstrated that for modern parallel‐plate chambers (perhaps because of improved manufacturing techniques) this is no longer as much of an issue. A measured gradient correction factor is required for cylindrical chambers.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6]12,13 McEwen 14 showed that it is feasible to provide measured k Q factors for a large set of ion chambers. Kapsch et al 15 used crosscalibration in electron beams and 60 Co calibrations to show that measured chamber-to-chamber variation of perturbation factors for the Roos, Markus, and Advanced Markus chamber types in cobalt-60 are now less than 1.1% within a single chamber type. Kapsch and Gomola 2 recently showed that chamber-to-chamber variation of k Q factors in photon beams is no longer as significant (less than 0.7% spread in values for ten chambers of each type), at least for two chamber types from one manufacturer.…”
Section: Introductionmentioning
confidence: 99%